Ki-67 and p53 expression as a predictive marker for early postoperative recurrence in pancreatic head cancer - Kim, Hohyun (Ann Surg Treat Res, 2015)
PURPOSE: This study aimed to evaluate the clinical significance of Ki-67 and p53 expressions in patients with pancreatic head cancer. METHODS: Between May 2008 and April 2013, immunohistochemical staining for Ki-67 and p53 was performed in 34 patients with pancreatic head cancer (ductal adenocarcinoma). All 34 patients underwent pancreaticoduodenectomy at Chonnam National University Hwasun Hospital, Hwasun, Korea. Clinical and histopathological characteristics were analyzed, relative to p53 expression. RESULTS: Thirty (88.2%) and twenty-one (61.7%) of the 34 pancreatic head cancers exhibited positive expression of Ki-67 and p53, respectively. Patients expressing Ki-67 and p53 experienced more frequent tumor recurrences within 1 year after surgical resection (P = 0.003 and P = 0.030, respectively). However, no correlation was detected between Ki-67 and p53 expression. Ki-67 expression was correlated with pathological grade, lymph node metasatsis, and clinical stage (P < 0.05). Importantly, Ki-67 was the independent predictive factor for postoperative recurrence within 1 year in both univariable and multivariable analyses (odds ratio, 27.219; 95% confidence interval, 1.403-528.135; P = 0.029). CONCLUSION: The expression of Ki-67 and p53 are significantly related to early postoperative recurrence within 1 year after surgical resection in pancreatic head cancer. Especially, Ki-67 was the independent predictive factor for postoperative recurrence within 1 year. Therefore, immunohistochemical staining for Ki-67 and p53 may be applied as a predictive marker for early postoperative recurrence in pancreatic head cancer.